Manhattan transfer - Dos Passos, John, 1896-1970. (Boston : Houghton Mifflin, 1953)
A thread of continuity binds these vignettes of incidents and characters living in New York City in the 1920's.
Ferryslip -- Metropolis -- Dollars -- Tracks -- Steamroller -- Great lady on a white horse -- Longlegged jack of the Isthmus -- Nine days' wonder -- Fire engine -- Went to the animals fair -- Five statutory questions -- Rollercoaster -- One more river to Jordan -- Rejoicing city that dwelt carelessly -- Nickelodeon -- Revolving doors -- Skyscraper -- The burthen of Nineveh.
Adult.
Adult
Keywords: New York (N.Y.) -- History -- 1898-1951 -- Fiction; New York (N.Y.) -- History -- Fiction